Minimal impact of recent decline in C4 vegetation abundance on atmospheric carbon isotopic composition - Lavergne,A; Harrison,SP; Atsawawaranunt,K; Dong,N; Prentice,IC (Communications Earth & Environment, 2026)
Changes in atmospheric carbon dioxide concentrations, climate, and land management influence the abundance and distribution of C3 and C4 plants, yet their impact on the global carbon cycle remains uncertain. Here, we use a parsimonious model of C3 and C4 plant distribution, based on optimality principles, combined with a simplified representation of the global carbon cycle, to assess how shifts in plant abundances driven by carbon dioxide and climate affect global gross primary production, land-based carbon isotope discrimination, and the isotopic composition of atmospheric carbon dioxide. We estimate that the proportion of C4 plants in total biomass declined from about 16% to 12% between 1982 and 2016, despite an increase in the abundance of C4 crops. This decline reflects the reduced competitive advantage of C4 photosynthesis in a carbon dioxide-enriched atmosphere. As a result, global gross primary production rose by approximately 16.5 ± 1.8 petagrams of carbon, and land-based carbon isotope discrimination increased by 0.017 ± 0.001‰ per year. Accounting for changes in C3 and C4 abundances reduces the difference between observed and modelled trends in atmospheric carbon isotope composition, but does not fully explain the observed decrease, pointing to additional, unaccounted drivers.